DISCRETIONAL ACCRUAL AND OWNERSHIP ON CORPORATE PERFORMANCE WITH FIRM VALUE AS MEDIATION: EVIDENCE FROM CONSUMPTION GOOD AND BASIC INDUSTRY CHEMISTRY IN INDONESIA STOCK EXCHANGE - Indrayati, Basuki Rahmat, Ludfi Djajanto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study analyzes and empirically examines the impact of earnings management, managerial ownership and public ownership on corporate performance and corporate value in food and beverage companies and basic chemical industries in the Indonesian stock exchange. Data analysis with multiple linear regression and path analysis with a population of consumer goods companies and basic chemical industries listed on the Indonesian stock exchange in 2018-2019 with a sample of 115 companies. The results showed that the variables of earnings management, corporate governance (managerial ownership and public ownership) had a significant effect on corporate value and corporate performance. Future research is expected to increase the research and macroeconomic and CSR variables that provide a comprehensive picture of the research results. Minimizing earnings management is expected to improve corporate performance and corporate value. As well as the effect of ownership can also increase corporate performance and corporate value.